SEPRES: Intensive Care Unit Clinical Data Integration System to Predict Sepsis - Chen, Qiyu; Li, Ranran; Lin, ChihChe; Lai, Chiming; Huang, Yaling; Lu, Wenlian; Li, Lei (Applied Clinical Informatics, 2023)
Background The lack of information interoperability between different devices and systems in the intensive care unit (ICU) hinders further utilization of data, especially for early warning of specific diseases in the ICU.Objectives We aimed to establish a data integration system. Based on this system, the sepsis prediction module was added to compose the Sepsis PREdiction System (SEPRES), where real-time early warning of sepsis can be implemented at the bedside in the ICU.Methods Data are collected from bedside devices through the integration hub and uploaded to the integration system through the local area network. The data integration system was designed to integrate vital signs data, laboratory data, ventilator data, demographic data, pharmacy data, nursing data, etc. from multiple medical devices and systems. It integrates, standardizes, and stores information, making the real-time inference of the early warning module possible. The built-in sepsis early warning module can detect the onset of sepsis within 5 hours preceding at most.Results Our data integration system has already been deployed in Ruijin Hospital, confirming the feasibility of our system.Conclusion We highlight that SEPRES has the potential to improve ICU management by helping medical practitioners identify at-sepsis-risk patients and prepare for timely diagnosis and intervention.
Keywords: sepsis; information system; intensive care units